Double Vision and Gait Ataxia in an Immunocompetent 9-Year-Old Girl With Intracranial Phaeohyphomycosis. Issue 3 (September 2021) - Pareek, Aishwarya V.; Lotze, Timothy E.; Demmler, Gail; Mohila, Carrie A.; Tran, Brandon; Shah, Veeral S.
Abstract : Abstract: A 9-year-old girl presented with morning headaches associated with vomiting, gait ataxia, and facial and ocular motor nerve palsies. Her initial imaging was concerning for demyelinating disease. After extensive infectious and rheumatologic workup returned negative, she was treated twice with intravenous immunoglobulin and intravenous steroids with near-complete resolution each time. She returned, however, with worsening neurologic deficits and imaging revealing focal ischemic infarction in the brainstem as well as new-onset hydrocephalus. A multispecialty workup was initiated without conclusive diagnosis. A novel, noninvasive test for plasma cell-free DNA established a diagnosis of Cladophialophora bantiana that was confirmed and validated by a brain biopsy taken during a clinical decompensation. Treatment was initiated with systemic voriconazole and intraventricular amphotericin B.